Raiders, Sultans, and the Legacy of Conquest: Byzantine Perspectives on the Ottoman Expansion - Bedirhanoğlu, Hüseyin Erkan (My University, 2024)
The transition from the Byzantine Empire to the Ottoman Empire marks a pivotal period in history, characterized by cultural exchange, conflict, and territorial expansion. This article attempts to examine Byzantine perspectives on the emergence and growth of the Ottoman Empire, primarily relying on the narrations from the works of Byzantine historians Chalkokondyles and Doukas. By analyzing their accounts, it becomes evident that the Byzantines viewed the Ottomans through a complex lens, acknowledging their military prowess while also condemning their methods of conquest. Key themes explored include the origins of the Ottomans, the tactics of Ottoman cavalry raiders, and the portrayal of Ottoman rulers. Contrary to the notion of Ottoman warriors as holy crusaders, Chalkokondyles and Doukas depict them as economically motivated plunderers, driven by a desire for wealth and slaves rather than religious motivations. Additionally, the Byzantine historians offer varied assessments of Ottoman sultans, praising those who exhibited goodwill towards the Byzantine Empire while criticizing those who posed a threat. Ultimately, this analysis challenges prevailing narratives about the Ottomans and underscores the importance of Byzantine sources in shaping our understanding of this transformative era in history.
Keywords: Chalkokondyles, Ottoman Empire, Byzantine Empire, Raiders, Doukas